Circular dichroism, molecular modeling, and serology indicate that the structural basis of antigenic variation in foot-and-mouth disease virus is alpha-helix formation. - France, L L (1994)
Seven antigenic variants obtained from a single field isolate of foot-and-mouth disease virus, serotype A12, differ only at residues 148 and 153 in the immunodominant loop of viral protein VP1. Synthetic peptides corresponding to the region 141-160 are highly immunogenic. UV circular dichroism shows that (i) in aqueous solution the peptides are nearly identical, but in 100% trifluoroethanol they display helix-forming properties which correlate well with their serological crossreactivities for anti-peptide sera, and (ii) these properties are insensitive to substitutions at position 153, except for proline, but are highly sensitive to substitutions at position 148. This pattern can be explained by the effects of these substitutions on the amphiphilic character and positions of helices postulated in the region 146-156. Molecular models indicate that residues 147, 148, 150, 151, 153-155, and 157 are most likely to interact with residues of the antibody paratopes. The data are consistent with the existence of an inverse gamma-turn around Pro-153, and a beta-turn at the cell-attachment site at residues 145-147.